Evaluation of the risk of bias in non-randomized studies of interventions (ROBINS-I) and the 'target experiment' concept in studies of exposures: Rationale and preliminary instrument development. (November 2018) - Morgan, Rebecca L.; Thayer, Kristina A.; Santesso, Nancy; Holloway, Alison C.; Blain, Robyn; Eftim, Sorina E.; Goldstone, Alexandra E.; Ross, Pam; Guyatt, Gordon; Schünemann, Holger J.
Abstract: Assessing the risk of bias (RoB) of individual studies is a critical part in determining the certainty of a body of evidence from non-randomized studies (NRS) that evaluate potential health effects due to environmental exposures. The recently released RoB in NRS of Interventions (ROBINS-I) instrument has undergone careful development for health interventions. Using the fundamental design of ROBINS-I, which includes evaluating RoB against an ideal target trial, we explored developing a version of the instrument to evaluate RoB in exposure studies. During three sequential rounds of assessment, two or three raters (evaluators) independently applied ROBINS-I to studies from two systematic reviews and one case-study protocol that evaluated the relationship between environmental exposures and health outcomes. Feedback from raters, methodologists, and topic-specific experts informed important modifications to tailor the instrument to exposure studies. We identified the following areas of distinction for the modified instrument: terminology, formulation of the ideal target randomized experiment, guidance for cross-sectional studies and exposure assessment (both quality of measurement method and concern for potential exposure misclassification), and evaluation of issues related to study sensitivity. Using the target experiment approach significantly impacts the process for how environmental and occupational health studies are considered in the Grading of Recommendations Assessment, Development and Evaluation (GRADE) evidence-synthesis framework.